Temporal bone pneumatization: A scoping review on the growth and size of mastoid air cell system with age. - Okikioluwa Stephen Aladeyelu; Kehinde Samuel Olaniyi; Samuel Oluwaseun Olojede; Wonder-Boy Eumane Mbatha; Andile Lindokuhle Sibiya; Carmen Olivia Rennie (PLoS ONE)
The interest in the mastoid air cell system arose from the association between temporal bone aeration and otitis media. Its size and growth have been considered when planning chronic and middle ear surgeries. The objective of this review was to explore the literature on the size of mastoid air cells with age, highlighting various growth rates reported and mapping out areas yet to be fully understood for further research. A three-step systematic search was conducted for available literature on the subject matter viz; Google Scholar, Medline, Cochrane Library, and PubMed. Eligibility criteria guided the study selection, and eligible studies were subjected to appraisal using screening and quantitative criteria of mixed-method appraisal tool. A data extraction form was developed to extract information from eligible studies. Nine studies met the eligibility criteria. 55.6% of the included studies were conducted among the east and south Asian population, 33.3% were conducted among Scandinavians, and 11.1% in South America. Age groupings varied among studies; 33.3% utilized 1-year age grouping, 33.3% utilized 5-year age grouping, 11.1% utilized 10-year age grouping. In reporting the size of mastoid air cells across age groupings, 66.7% utilized area, 22.2% utilized volume, while 11.1% utilized both area and volume. Findings from this review showed that the mastoid air cells' size with respect to age differs among populations of different origins. The most common measurements were the area of air cells. The highest growth rate was reported up to 30 years. Findings also show the influence of sex on the size of mastoid air cells and growth rate with age, as females were reported to have larger air cells with rapid growth until puberty. However, the male mastoid air cell system continues a steady growth after puberty and becomes larger. Information still lacks in the volume of air cells in pediatric pneumatization.